STUDENTS’ PERCEPTIONS TOWARD THE USE OF WORDWALL AS A FORMATIVE ASSESSMENT IN ELT - Ranti Sabilla Anjani; Siti Lestari; Kusnadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT This study is to investigate students' perceptions about using Wordwall media as a formative assessment tool in learning English at SMP Negeri 37 Semarang. The subject of this study is 32 students of class VII H of SMP Negeri 37 Semarang in 2023. The data collection method uses questionnaires and interviews. Questionnaires were distributed to determine students' understanding and interviews were conducted to obtain in-depth responses so that the researchers could better describe and analyze students' perceptions of the Wordwall application as a learning tool. The results of this study show that almost all students are interested in using Wordwall as a formative assessment tool because it is easy to use, has an attractive design, and a variety of questions that made students want to use it. It can be concluded that the Wordwall can be used as an assessment tool in the future.